2010
DOI: 10.1371/journal.pone.0008636
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Cellulolytic Enzyme Genes from Representative Lineages of Termites and a Related Cockroach

Abstract: The relationship between xylophagous termites and the protists resident in their hindguts is a textbook example of symbiosis. The essential steps of lignocellulose degradation handled by these protists allow the host termites to thrive on a wood diet. There has never been a comprehensive analysis of lignocellulose degradation by protists, however, as it has proven difficult to establish these symbionts in pure culture. The trends in lignocellulose degradation during the evolution of the host lineage are also l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…Apart from two new GHs, the GH domains revealed in the present work were also found in microbial communities from lower and higher wood-feeding termites and Cryptocercus cockroaches (69,75), whereas GHF6 from Cellvibrio spp. appeared to be specific to the earthworm-derived communities studied.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Apart from two new GHs, the GH domains revealed in the present work were also found in microbial communities from lower and higher wood-feeding termites and Cryptocercus cockroaches (69,75), whereas GHF6 from Cellvibrio spp. appeared to be specific to the earthworm-derived communities studied.…”
Section: Discussionmentioning
confidence: 50%
“…However, compared to other invertebrates, e.g., marine bivalves (21) or termites (19,48,56,68,69,75), little is known about the enzymatic machinery of earthworm-associated microorganisms that allows them to deplete diverse polymeric lignocellulosic substrates at high rates. In this work, we established enrichment cultures in a minimal mineral medium with cellulose as the sole carbon and energy source and with fresh casts from earthworms as inocula.…”
Section: Discussionmentioning
confidence: 99%
“…59,60) Approximately 1,000 cDNA clones per host species were sequenced, and it was found that about 10% of the clones in each sample belonged to the glycosyl hydrolase families (GHFs) such as GHF5, 7, 10, and 45. These included cellulases (endoglucanase and cellobiohydrolase) and hemicellulases.…”
Section: Metagenomics and Metatranscriptomics Of Termite Gut Micmentioning
confidence: 99%
“…Although, we have yet to identify specific conditions allowing strain TAV2 to grow in xylan as a sole C source (Wertz et al, 2012), our integrated approach identified genes and proteins involved in lignocellulose degradation, specifically the enzymes acetylxylan esterase, xylan a-1,2-glucuronosidase and xylose isomerase, the later being responsible for converting xylose into xylulose, which enters the PPP (White, 2007). Because much of investigation in termite guts have targeted cellulose degradation through biochemical characterization of host celullases (Watanabe and Tokuda, 2010), gene expression of glycosyl hydrolases by protists (Todaka et al, 2007(Todaka et al, , 2010, and metagenomic (Warnecke et al, 2007) and proteomic (Burnum et al, 2011) approaches, the understanding of xylan hydrolysis remains virtually unexplored. Our results reveal an important and perhaps compartmentalized, ecological role for the TAV2 population on the debranching of xylan residues.…”
Section: Discussionmentioning
confidence: 99%